Finite element method (FEM) and impulse response method (IRM) analysis of circular ultrasonic transducers - P. KIEŁCZYŃSKI (Archives of Acoustics)
Circular transducers with axially-symmetric vibrational profiles were considered. Vibrational patterns of transducer structures were calculated using the Finite Element Method. Analytical formulas for the impulse response function h(X, t) for circular transducers and vibration velocity profiles, approximated by linear and quadratic polynomials, on the finite element (annulus) were established. These formulas enable accurate calculations of acoustic field distributions in near and far-field, respectively. Calculated profiles of an acoustic field were compared with the experimental data.